EFEK TELEMEDICINE PADA MASYARAKAT (Kajian Hukum Media McLuhan: Tetrad) - Ganiem, Leila Mona (Master of Communication Science Program, Universitas Diponegoro, 2020)
Telemedicine is ‘healing at a distance’ uses information and communication technology in healthcare. The user and the provider of telemedicine increase sharply especially during covid-19. To understand the effect of media to the society, McLuhan created the Laws of Media or tetrad. The objective of this study is to analyse the effects of telemedicine on society by extracting McLuhan law of media or tetrad: enhancement, obsolencense, flip/reverse, and retrieve. This research method uses a qualitative descriptive by reviewing 23 relevant international journals discussing telemedicine, tetrad, or health services published from 2015-2020. The result, telemedicine enhance accessibility, flexibility, different types of communication devices, lower costs, management planning prior to patient movement, time saving. Telemedicine make obsolencense on face-to-face doctor-patient interaction, limited verbal nonverbal communication, clinic or hospital, face-to-face replaced with online peerto peer mentoring, potential reduce on confidentiality and privacy. Telemedicine reverse appears to provide equal opportunities for everyone to get health services but when pushed to the limit of its potential, telemedicine can only have an optimal impact on good communicator, digital divide, and financial capability. Telemedicine retrieve the presence of doctor at home virtually, allow virtual waiting room.